Pengaruh Terapi Murotal Al-Quran Surah Ar Rahman Terhadap Kestabilan Saturasi Oksigen BBLR Dengan Asfiksia di Ruang NICU - Ais Izza Fadhilah; Falasifah Ani Yuniarti; Rina Prawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: LBW babies face difficulties adapting to life outside the womb because their organs, such as the lungs, heart, kidneys, liver and digestive system, are not fully mature. The neonatal period is the most vulnerable period for a baby's survival, and one of the causes of newborn deaths is asphyxia. One of the complementary therapy techniques that can be used to increase saturation and hemodynamics in LBW babies is music therapy and murrotal therapy. Research method: The research method used in the intervention is a case report using the intervention method. The research was carried out in the NICU room at Tjitrowardojo Regional Hospital, Purworejo, when the research was carried out on 01-05 May 2024. The research participants were one neonate patient with a diagnosis of LBW accompanied by asphyxia. Oxygen saturation measurements were carried out before and after Murottal Surat Ar-Rahman Therapy was given. Results: After being given the Murotal Al-Qur'an Surah Ar-rahman therapy intervention within 30 minutes for five days, there was an increase in oxygen saturation in LBW babies with asphyxia on the first day from 88% to 93%, and on the fifth day there was an increase in oxygen saturation from 99 % becomes 100%.Conclusion: Murottal Al-Qur'an Surah Ar-Rahman therapy has a positive effect on oxygen saturation in patients with LBW accompanied by asphyxia